Survey of Assessing Pain in Clinical Practice and Applicability of a New Assessment - (:unkn) unknown (My University, 2016)
ABSTRACT SURVEY OF ASSESSING PAIN IN CLINICAL PRACTICE AND APPLICABILITY OF A NEW ASSESSMENT by Michelle Konz The University of Wisconsin-Milwaukee, 2016 Under the Supervision of Professor Joyce Engel, PhD Aims The purpose of this study is to identify pain assessments that are being used to measure an individual’s pain experience and to discover how occupational therapists are currently assessing pain in youths who have complex communication needs with a developmental disability (DD). Methods Phase 1: A literature review was conducted through the use of electronic databases to research 17 different methods of pain assessment to create descriptive charts to aide in pain assessment. Phase 2: A 13-question survey was completed by 19 occupational therapists selected through a convenience sample, to determine how pain is currently being assessed for youths who have complex communication needs. Results Phase 1: Three charts were compiled of pain assessments. Each pain assessment has different aspects, but no one measure covers all pain domains and are not accessible. Phase 2: The results indicated that 12 out of 19 respondents do not assess pain. Conclusion In Phase 1, it was determined current pain assessments do not gather a holistic report of pain experiences and are not fully accessible. Survey results suggest that pain is not assessed by more than half of the OTs in this study. Creation of a new pain assessment should be completed in order to fulfill the need of an accessible self-report assessment for youths who have complex communication needs with a DD. Keywords: Occupational therapy, pain assessment, self-report, disability, youths
Keywords: Assessment; Disability; Occupational Therapy; Pain; Self-report; Youths